2012
DOI: 10.1186/1756-9966-31-11
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DNA damage-induced 45 α gene contributes to esophageal squamous cell cancer by promoter hypomethylation

Abstract: BackgroundEnvironmental factors-induced dysfunction of esophageal squamous epithelium, including genomic DNA impairment and apoptosis, play an important role in the pathogenesis of esophageal squamous cell cancer. DNA damage-induced 45α (GADD45α) has been found promoting DNA repair and removing methylation marker, Therefore, in this study we will investigate whether GADD45α expression is induced and its mechanism in esophageal squamous cell cancer.MethodsTwo human esophageal squamous cell lines (ESCC), ECA109 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…However, as few studies have described the mechanisms mediating GADD45A expression in ESCC, it is not known whether p53 regulates GADD45A expression in this cancer type (22). Notably, the present study found that GADD45A, but not p53, was able to predict the prognosis of patients with ESCC.…”
Section: Discussionsupporting
confidence: 54%
“…However, as few studies have described the mechanisms mediating GADD45A expression in ESCC, it is not known whether p53 regulates GADD45A expression in this cancer type (22). Notably, the present study found that GADD45A, but not p53, was able to predict the prognosis of patients with ESCC.…”
Section: Discussionsupporting
confidence: 54%
“…Global methylation levels were measured using a Methylamp Global DNA Methylation Quantification Ultra kit (Epigentek Group Inc., New York, NY, USA) as previously described . According to the manufacturer's instructions, DNA is immobilized to the strip well specifically coated with a DNA affinity substance.…”
Section: Methodsmentioning
confidence: 99%
“…50 According to the manufacturer's instructions, the methylated fraction of DNA can be recognized by a 5-methylcytosine antibody and quantified through an ELISA-like reaction. The amount of methylated DNA is proportional to the OD intensity.…”
Section: Methodsmentioning
confidence: 99%